I have following equations:

$$\frac{1}{((a_1 - 1) f + 1)} + \frac{1}{((a_2 - 1) f + 1)} -k = 0$$ $$\frac{1}{((a_1 - 1) f + 1)} + \frac{1}{((a_1 - 1) f + 1)} + ... + \frac{1}{((a_n - 1) f + 1)} -k = 0$$

which can be written as:

$$(\sum_{i=1}^n \frac{1}{((a_i - 1) f + 1)}) - k = 0; n>=2$$

For each of $n$ values, I get polynomials of 2nd, 3rd, ... nth grade.

Is it easy to generalize this formula to get it somehow in this form?:

$$(\sum_{i=0}^n f^{i}(unknown))=0; n>=2$$

n=2 (and assuming $b_n=a_n-1$) I get:

$$b_1 b_2 f^2 (-k)+f \left(b_1 (-k)-b_2 k+b_1+b_2\right)-k+2=0$$

n=3 (and assuming $b_n=a_n-1$) I get:

$$b_1 b_2 b_3 f^3 (-k)+f^2 \left(b_1 b_2 (-k)-b_3 b_2 k-b_1 b_3 k+b_1 b_2+b_3 b_2+b_1 b_3\right)+f \left(b_1 (-k)-b_2 k-b_3 k+2 b_1+2 b_2+2 b_3\right)-k+3=0$$

n=4 (and assuming $b_n=a_n-1$) I get:

$$b_1 b_2 b_3 b_4 f^4 (-k)+f^3 \left(b_1 b_2 b_3 (-k)-b_1 b_4 b_3 k-b_2 b_4 b_3 k-b_1 b_2 b_4 k+b_1 b_2 b_3+b_1 b_4 b_3+b_2 b_4 b_3+b_1 b_2 b_4\right)+f^2 \left(b_1 b_2 (-k)-b_3 b_2 k-b_4 b_2 k-b_1 b_3 k-b_1 b_4 k-b_3 b_4 k+2 b_1 b_2+2 b_3 b_2+2 b_4 b_2+2 b_1 b_3+2 b_1 b_4+2 b_3 b_4\right)+f \left(b_1 (-k)-b_2 k-b_3 k-b_4 k+3 b_1+3 b_2+3 b_3+3 b_4\right)-k+4=0$$

And so on.. Not sure if there is some general solution to this, so I can easily construct equation without the need to multiply and group params.

  • $\begingroup$ First of all, your equations would look much simpler if you make a substitution $b_n=a_n-1$. $\endgroup$
    – yarchik
    Commented Jul 22, 2019 at 12:09
  • $\begingroup$ @yarchik thanks for suggestion. will try now :) $\endgroup$ Commented Jul 22, 2019 at 12:15

1 Answer 1


OK, after simplifying by using suggestion from comments, I think I have it now:


Just don't know if this is proper way to express all $i$ combinations of $b_1...b_n$ elements


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.